Refurbished or Remanufactured?—An Experimental Study on Consumer Choice Behavior - Chen, Yao; Wang, Jinfei; Jia, Xuening (Frontiers in Psychology, 2020)
Remanufacturing is one of the important means to achieve circular economy and improve the reuse of resources. But, compared with the reuse of old parts, most ordinary Chinese consumers are not familiar with remanufacturing. Because of this, the development of China's remanufacturing industry is hindered. This paper introduces two kinds of consumer goods with different attributes, namely MP4 (the hedonic product) and cartridge (the functional product). The empirical study on the consumption behavior of Chinese consumers when they are faced with a variety of recycling options was performed. Empirical studies are divided into two stages: participants need to give hypothetical purchase decisions when facing situations of two products (new products and remanufactured products) and three products including refurbishment products, respectively. This paper analyzes the purchase intention and decision-making process of Chinese consumers for remanufactured products, new products and refurbished products in these two situations. The consumers' willingness to pay for remanufactured products and refurbished products are also part of the study. The experimental results verify that consumers have a different selection mechanism for new products, remanufactured products and refurbished products, and there is also a certain relationship between this selection mechanism and the attributes of the product itself. The research shows that due to the different product attributes, consumers pay different attention to the environmental protection, quality, brand, price, new and old preferences of products. The result of the model shows that the choice behavior of different products and their willingness to pay are also affected by different levels of these attentions. Through the research results, this paper finds conclusions like refurbished products have an impact on the development of remanufactured products, consumers pay more attention to price, but do not pay attention to environmental protection. The conclusion of the study provides references and practical implications for Chinese remanufacturing enterprises to formulate market strategy, government to formulate relevant policies, and OEM production.